A 26-Year-Old Woman with Worsening Dyspnea: Look Closer, Think Critically - Koza, Yavuzer (J Cardiovasc Echogr, 2020)
Pulmonary hypertension due to congenital heart disease continues to be a diagnostic challenge despite modern diagnostic modalities. Herein, we report a 26-year-old woman with an incidentally documented patent ductus arteriosus and Eisenmenger syndrome. She presented with progressive dyspnea and exercise intolerance which was initially attributed to pulmonary embolus. She was started on macitentan and tadalafil therapy aiming to reduce the pulmonary vascular resistance with consideration for heart–lung transplantation should any further deterioration occur.